MAKING VOTESCOUNT IN ELECTION TECHNOLOGY ERA: A PROPOSED FRAMEWORK FOR NIGERIA’S FUTURE ELECTIONS TO ENHANCE GLOBAL STANDING - SHAIBU, M. T.; LANRE OLU-ADEYEMI; DAYO VICTOR OWOEYE (International Studies Journal)
The electoral process, been a recurrent political ceremony, holds central significance within any democratic framework; however, the realization of honest vote counting during elections has presented persistent challenges within the context of Nigeria.Readings from extant literature stronglyrevealed there is consensus forutilization of technologies forvoters’accreditation, voting and results transmission with electoral institutions handling results collation and declaration but this has continue to cast doubt on theintegrity of the electoral processand have undermined the significance of votes as the political environment experienced in the Nigeria's 2023 elections showed that the issue of credibility remain unresolved,underliningthe gap between expectation and election outcome. This paper examines the 2023 election procedures cum the nature of the political climate experienced and frames an Automated Election Management System (AEMS) model credible for promoting conducive politico-climate tooptimise the significance of votes. The qualitative technique was adopted. This paper argues that except the entire election process in Nigeria is automated, votes would still not count in future elections. The fate of democracy, the country’s global standing will remain in doubt and her foreign policy will continually glitch.This paper is significant as it contributes to existing literature on the imperative of automated election processin promoting democratic principles.It equally serves as policy guide for domestic, regional and international interventions on election matters.